Influence of dual task in functional performance in institutionalized and not institutionalized elderly - Almeida, Marineide do Sacramento (2018)
This cross-sectional study evaluated the influence of dual task in functional performance of institutionalized and not institutionalized elderly. For it, they performed simple and dual task activities, with a lower performance in the dual tasks and in the institucionalized elderly, and it was concluded that the addition of a double task reduces functional performance, especially in the institucionalized elderly.